Hubungan Tingkat Pengetahuan Dengan Kepatuhan Penggunaan Obat Pada Pasien Tuberculosis Di Puskesmas Buhit Kabupaten Samosir - Masyitah, Cut; Widya Safitri; Syarifah Roslianizar (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Abstract Patient non-compliance with the provisions and duration of regular treatment to achieve healing as a result of low levels of community knowledge. The healing process of tuberculosis patients is quickly realized, if there is cooperation between patients and their families with health service providers. The purpose of this study was to determine the relationship between the level of knowledge and compliance with taking anti-tuberculosis drugs in TB patients at the Buhit Health Center, Samosir District. The population in this study were all pulmonary TB patients and the sample was a total population of 56 respondents. The data obtained using a research instrument in the form of a questionnaire were then processed and analyzed using the chi-square statistical test. Based on the results of the study, it showed that 1) the level of knowledge of tuberculosis patients was mostly good knowledge at 57.1%, 2) Compliance with taking medication in tuberculosis patients was 50% each, 3) there was a relationship between the level of knowledge and compliance with taking anti-tuberculosis drugs. From the results of this study, it is hoped that patients will be quick and avoid complications from the disease they suffer from, so pulmonary TB patients are expected to always comply with the recommendations given by doctors or other officers and also maintain a healthy lifestyle.